A Rapid Culture Method for the Detection of Campylobacter from Water Environments - Strakova, Nicol; Korena, Kristyna; Gelbicova, Tereza; Kulich, Pavel; Karpiskova, Renata (International journal of environmental research and public health, 2021)
The natural environment and water are among the sources of Campylobacter jejuni and Campylobacter coli. A limited number of protocols exist for the isolation of campylobacters in poorly filterable water. Therefore, the goal of our work was to find a more efficient method of Campylobacter isolation and detection from wastewater and surface water than the ISO standard. In the novel rapid culture method presented here, samples are centrifuged at high speed, and the resuspended pellet is inoculated on a filter, which is placed on Campylobacter selective mCCDA agar. The motile bacteria pass through the filter pores, and mCCDA agar suppresses the growth of background microbiota on behalf of campylobacters. This culture-based method is more efficient for the detection and isolation of Campylobacter jejuni and Campylobacter coli from poorly filterable water than the ISO 17995 standard. It also is less time-consuming, taking only 72 h and comprising three steps, while the ISO standard method requires five or six steps and 144-192 h. This novel culture method, based on high-speed centrifugation, bacterial motility, and selective cultivation conditions, can be used for the detection and isolation of various bacteria from water samples.
Keywords: filtration; Culture Media; wastewater; centrifugation; Campylobacter coli; Water; Campylobacter jejuni; surface water; culture method; Campylobacter; voda; kultivační média